Psychophysiological markers of athlete burnout: a call to arms - Moore, Lee; Isoard-Gautheur, Sandrine; Gustafsson, Henrik (International Journal of Sports Medicine, 2024)
Burnout is a growing problem in high-performance sport and has negative consequences for athletes (e.g., mental ill-health). It is therefore important to effectively monitor athlete burnout to aid intervention efforts. While self-report measures are available (e.g., athlete burnout questionnaire), the limitations associated with these measures (e.g., social desirability bias) means that objective physiological markers may also be useful. Thus, this article critically discusses potential biomarkers of athlete burnout, drawing on research inside and outside of sport to offer an overview of the current state-of-the-art in this research area. First, it outlines what athlete burnout is, its deleterious consequences, and discusses existing psychological assessments. The article then critically discusses literature on hypothalamic-pituitary-adrenal axis (e.g., salivary cortisol) and autonomic nervous system (e.g., heart rate variability) indices of burnout, highlighting some promising biomarkers for future research (e.g., salivary cortisol at bedtime, vagally-mediated heart rate variability at rest). Finally, the article concludes by highlighting key considerations and offering recommendations for future research (e.g., use of more homogenous methods in assessing burnout and physiological parameters). As a result, the intention of this article is to spark more higher quality research on the psychophysiology of athlete burnout, thereby helping tackle this prominent issue in high-performance sport.
Keywords: Biomarkers; Exhaustion; Mental Health; Sport Devaluation; Well-Being